(untitled) (Anwer Khan Modern Medical College Journal, 2020)
Background: Effective analgesia is important after laparoscopic cholecystectomy. Paracetamol have been used extensively as alternatives, and it seems that they are more effective for mild to moderate pain control postoperatively. As laparoscopic Cholecystectomy poses moderate pain, in this study we compare the quality of analgesia and side effects of paracetamol versus pethidine for post-operative analgesia after laparoscopic cholecystectomy. Objectives: This study was designed to observe the effect of I.V. paracetamol and I.M. pethidine for analgesic efficacy in post-operative analgesia with their side effects in laparoscopic cholecystectomy. Material and method: Sixty (60) patients were selected in the pre anaesthetic check up room whose were going to be operated for laparoscopic cholecystectomy. Each patient in group A received intravenous paracetamol (1g/100ml)15mg/kg over 15minutes and group B received intramuscular pethidine (100mg)- 2mg/kg postoperatively. Results: In group A that was paracetamol group and group B that was pethidine group the visual analogue scale (VAS) almost similar but total analgesic consumption in pethidine group were slightly higher than paracetamol group and the respiratory rate were significantly lower in pethidine group. Conclusion: Our results indicate that IV paracetamol 15mg / kg has better analgesic potency and less side effects than 2 mg / kg IM pethidine for postoperative analgesia after laparoscopic cholecystectomy. Anwer Khan Modern Medical College Journal Vol. 11, No. 1: Jan 2020, P 46-53